LANDSCAPE AND PLANNING INTEGRATION TOWARDS A BETTER PUBLIC OPEN SPACE IN CHERAS RESIDENTIAL NEIGHBOURHOOD - Janice Yap Sheu Jun; Hussein, Hazreena (Journal of Surveying, Construction and Property, 2024)
Urban settlements are inherently incomplete without the strategic design of public open spaces, which are essential for enhancing the quality of life and providing numerous social, health, environmental, and economic benefits to residents. In Kuala Lumpur, rapid urbanization and inadequate residential planning have led to a decline in the quality of public open spaces, negatively impacting residents’ well-being. This situation highlights the critical need for a comprehensive approach to public open space design that addresses these issues and fosters community engagement and vitality. This study investigates the current state of public open spaces in Cheras, Kuala Lumpur, specifically focusing on Taman Mutiara Barat and Taman Taynton View. By analyzing the physical characteristics, social dynamics, and environmental factors of these areas, the study aims to propose design criteria for improving these spaces. Ultimately, the goal is to create vibrant and inclusive public open spaces that enhance the quality of life for residents of Cheras.